Combining UAS-TIR and GEM-2 Techniques for Focused Water Sampling and Isotope Geochemical Analysis at Two Mine Sites in Northern Finland - Ikonen, Juuso; Rauhala, Anssi; Tuomela, Anne; Postila, Heini; Kumpula, Timo; Korpelainen, Pasi; Pietilä, Raija; Valta, Riku-Olli; Lerssi, Jouni; Panttila, Hannu; Korkka-Niemi, Kirsti (Springer Science and Business Media LLC, 2025)
A combination of thermal infrared (TIR) images captured by uncrewed aircraft systems (UASs) and manual geophysical measurements with a GEM-2 device were used to better plan a water sampling campaign at an abandoned Au-Cu mine and an active Ni-Cu-PGE mine in the sub-arctic boreal zone in northern Finland. Anomalies from the TIR images and GEM-2 conductivity values were used to focus the water sampling. The hydrogeochemistry and isotopic compositions of oxygen (δ18O), hydrogen (δ2H), strontium (87Sr/86Sr), and sulfur (δ34S) were analyzed to better understand the flow regime of possible effluent waters at these mine sites. The TIR images were useful in pinpointing sites where groundwater and surface water were potentially interacting. This was confirmed with the oxygen and hydrogen isotopic data. Isotopic values for the two groundwater solutes used here (Sr and S), reflected the local geology and the biogeochemical environment at the mine sites. The electrical conductivity values obtained from the GEM-2 measurements were influenced by the local geochemistry, particularly the presence of conductive sulfide-bearing paraschist rock. The anomalies from the UAS-TIR and GEM-2 data revealed sampling sites well suited for tracking potential effluent waters at the two mine sites.